Medroxyprogesterone Acetate Impairs Amyloid Beta Degradation in a Matrix Metalloproteinase-9 Dependent Manner - Porter, Keyana N.; Sarkar, Saumyendra N.; Dakhlallah, Duaa A.; Vannoy, Mya E.; Quintana, Dominic D.; Simpkins, James W. (Frontiers in Aging Neuroscience, 2020)
Despite the extensive use of hormonal methods as either contraception or menopausal hormone therapy (HT), there is very little known about the potential effects of these compounds on the cellular processes of the brain. Medroxyprogesterone Acetate (MPA) is a progestogen used globally in the hormonal contraceptive, Depo Provera, by women in their reproductive prime and is a major compound found in HT formulations used by menopausal women. MPA promotes changes in the circulating levels of matrix metalloproteinases (MMPs), such as MMP-9, in the endometrium, yet limited literature studying the effects of MPA on neurons and astroglia cells has been conducted. Additionally, the dysregulation of MMPs has been implicated in the pathology of Alzheimer’s disease (AD), where inhibiting the secretion of MMP-9 from astroglia reduces the proteolytic degradation of amyloid beta. Thus, our hypothesis is that exposure to MPA disrupts proteolytic degradation of amyloid beta through the downregulation of MMP-9 expression and subsequent secretion. To assess the effect of progestins on MMP-9 and amyloid beta, in vitro, C6 rat glial cells were exposed to MPA for 48 hours and then the enzymatic, secretory, and amyloid beta degrading capacity of MMP-9 was assessed from the conditioned culture medium. We found that MPA treatment inhibited transcription of MMP-9, which resulted in a subsequent decrease in the production and secretion of MMP-9 protein, in part through the glucocorticoid receptor. Additionally, we investigated the consequences on amyloid beta-degrading activity and found that MPA treatment decreased proteolytic degradation of amyloid beta. Our results suggest MPA suppresses amyloid beta degradation in an MMP-9-dependent manner, in vitro, and potentially compromises the clearance of amyloid beta in vivo.